Anti-inflammatory effect of fluvastatin on polarized macrophages and its dependence on the mevalonate pathway - Muffova, Barbora; Kauerova, Sona; Paukner, Karel; Bartuskova, Hana; Poledne, Rudolf; Kralova Lesna, Ivana (Scientific reports, 2025)
The study focuses on the effects of fluvastatin on immunomarkers of the M1 and M2 macrophages and its direct role in macrophage (M0) polarization. Moreover, it investigates the dependency of immunomodulatory properties of fluvastatin on the mevalonate pathway. Macrophages (M0, M1, M2), differentiated from human blood monocytes, were treated with fluvastatin. Mevalonate and geranylgeranyl pyrophosphate intermediates were introduced to assess the mevalonate pathway dependence. The immunomarkers were evaluated with qPCR, ELISA, Griess assay, and flow cytometry. Fluvastatin significantly reduces the pro-inflammatory gene expression (NFκB, IL-1β, IL-6, iNOS) in M1 while enhancing the anti-inflammatory markers (Arg-1, TGFβ) in M2 macrophages. The production of the TNFα, IL-1β, and IL-6 cytokines is reduced in M1, and IL-10 production increased in M2 macrophages. Fluvastatin decreases the iNOS activity in M1 macrophages. The intermediates reverse the fluvastatin's effects on anti-inflammatory gene expression by M2 macrophages, cytokine production (by M1 and M2 macrophages), and iNOS activity (by M1 macrophages). Their impact on surface marker expression was somewhat limited. These findings demonstrate that fluvastatin exerts anti-inflammatory effects on polarized macrophages without affecting polarization per se and also highlight the dependency on the mevalonate pathway. This study deepens the understanding of statins' immunomodulatory mechanisms, suggesting potential applications in treating inflammatory diseases.
Keywords: kyselina mevalonová; cytokiny; Fluvastatin; fluvastatin; Cytokines; antiflogistika; Mevalonic Acid; Anti-Inflammatory Agents; lidé; Macrophages; Humans; makrofágy